Characteristics of a propagating, self-pulsing, constricted 'γ-mode-like' discharge. (19th January 2015) - Schröder, Daniel; Burhenn, Sebastian; de los Arcos, Teresa; Schulz-von der Gathen, Volker
Abstract: Investigations on the self-pulsing operation regime of a modified micro-scaled atmospheric pressure plasma jet ( μ -APPJ) are presented. Using a wedge-shaped electrode configuration, a self-pulsing behavior of the device is achieved, which is characterized by the repetitive ignition of a constricted ' γ -mode-like' discharge at the gas inlet, which propagates with the gas flow towards the nozzle, where it extinguishes. The ' γ -mode-like' feature coexists with the homogeneous alpha-glow. Synchronized voltage/current and optical emission measurements are presented in order to correlate the evolution of electrical quantities such as voltage, current, dissipated power and phase with changes in the discharge structure. First insights are gained into the underlying discharge dynamics responsible for a stable self-sustainment, propagation and extinction of the constricted discharge. The results indicate that processes induced by helium metastables play a major role. Maximal electron densities on the order of n e  = 3.2 · 10 12  cm −3 and dissipated power of 18.9 W are achieved in this novel operation regime.